THE EFFECT OF THE VALUE OF INTANGIBLE ASSETS ON THE VALUE OF THE COMPANY WITH AUDITOR QUALITY AS A MODERATING VARIABLE - Abdillah, Muhammad Yunus Abdillah; Yulinartati , Yulinartati; Gardina Aulin Nuha (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the influence of the value of intangible assets on the value of the company, with auditor quality as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange during the period 2021–2024. The main problem lies in how intangible assets affect investors' perception of a company's value, as well as the role of auditor quality in strengthening those relationships. This study uses a quantitative approach based on secondary data with multiple linear regression analysis methods and moderation interaction tests. The results of the study show that the value of intangible assets has a positive and significant effect on the value of the company. In addition, the quality of auditors is proven to strengthen the relationship, where companies audited by the Big Four Public Accounting Firms (KAP) show greater influence. These findings emphasize the importance of optimal management of intangible assets and the selection of high-quality auditors in increasing the company's value in the eyes of investors.